Proceedings of the Ocean Drilling Program 1992
DOI: 10.2973/odp.proc.sr.127128-2.239.1992
|View full text |Cite
|
Sign up to set email alerts
|

Neogene Kinematics in the Japan Sea Region and Volcanic Activity of the Northeast Japan Arc

Abstract: Deep sea drilling in the Japan Sea during ODP Legs 127 and 128 brought new constraints to the timing and dynamics of backarc opening. The nature and age of the oceanic basement as well as the recovered lithology allow us to present new reconstructions from 25 Ma to the present. On-land deformation data as well as the offshore crustal structure and timing of volcanic events are the major constraints we use. The Japan Sea opened as a complex pull-apart basin in a dextral shear zone that extends more than 2000 km… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
1
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 54 publications
1
104
1
1
Order By: Relevance
“…After a period of transpressional dextral strike-slip crustal faulting, from the Oligocene to the Middle Miocene, a drastic change to transtensional deformation occurred at 10 m.y., which is contemporaneous with the end of the opening of the Japan Sea and Kurile Basin (Jolivet and Tamaki, 1992). If both events are related, then about 400 km of dextral displacement are expected .…”
Section: Regional Settingmentioning
confidence: 99%
“…After a period of transpressional dextral strike-slip crustal faulting, from the Oligocene to the Middle Miocene, a drastic change to transtensional deformation occurred at 10 m.y., which is contemporaneous with the end of the opening of the Japan Sea and Kurile Basin (Jolivet and Tamaki, 1992). If both events are related, then about 400 km of dextral displacement are expected .…”
Section: Regional Settingmentioning
confidence: 99%
“…Hayashida et al (1991) suggested a possibility that the drifting process of Southwest Japan involved a southward translation before 16 Ma and clockwise rotation of about 50Ā° between 16 and 14 Ma. Jolivet and Tamaki (1992) inferred that coherent rotation of Southwest Japan of about 30Ā° occurred in transtensional drift of the Japanese Islands to the south, assuming additional clockwise rotation of local small blocks within Southwest Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on Cenozoic stratig raphy of the Japanese Islands , 40Ar -39Ar dating of submarine volcanic rocks from the Japan Sea (Kaneoka et al, 1990(Kaneoka et al, , 1992, and results of Ocean Drilling Project (Jolivet and Tamaki, 1992) The outline of geology of Oki-Dogo Island (Fig. 2), combined with previous works and cur rent age determinations, is as follows: Basement rocks of Oki-Dogo Island are Prot erozoic metamorphic rocks whose Nd-Sm whole rock ages are about 2 Ga (Tanaka and Hoshino, 1987), and granitic rocks of Palaeozoic and Neo gene age (Tainosho et al, 1991).…”
Section: Tectonic Settingmentioning
confidence: 99%